PedsCases - A Learning Module for Evaluation of Pediatric Short Stature and Delayed Puberty for Medical Students - Peter MacPherson; Seth Marks; Robert Couch (Association of American Medical Colleges, 2010)
Abstract This resource is a podcast-based learning module that reviews an approach to the evaluation of short stature for medical students. In addition, a multistep case outlines a thorough approach to evaluating delayed puberty in a pediatric patient. This resource is a part of PedsCases, a comprehensive web-based educational series that focuses on the core objectives of undergraduate pediatric education with extensive student involvement. PedsCases was created for and by medical students to provide an opportunity for active self-directed learning in pediatrics. The learning modalities available include questions, flash card-type quizzes, multistep clinical cases, and podcasts. PedsCases has been integrated into the third-year undergraduate pediatric medical education curriculum at the University of Alberta. It is one of the main sources recommended to students to assist in covering the core objectives of the clinical pediatric rotation and in preparing for the final examinations.